Comparison of mid-term clinical outcome in heart transplantation patients using mycophenolate mofetil vs. enteric-coated mycophenolate sodium - Jeon, Kina; Kim, Darae; Choi, Jin-Oh; Cho, Yang Hyun; Sung, Kiick; Oh, Jaewon; Cho, Hyun Jai; Jung, Sung-Ho; Lee, Hae-Young; Park, Jin Joo; Choi, Dong-Ju; Kang, Seok-Min; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Mycophenolate mofetil (MMF) is a prodrug of mycophenolic acid (MPA) and a key immunosuppressant for improving graft survival in patients with heart transplantation (HTx). However, dose reduction or interruption is occasionally needed due to gastrointestinal (GI) side effects. Enteric-coated mycophenolate sodium (EC-MPS) is an alternative form of MPA delivery to improve (GI) tolerability. In the present study, the efficacy of EC-MPS compared with MMF in HTx patients was investigated. Methods: In this retrospective study, the Korean Organ Transplant Registry (KOTRY) data were used to analyze the efficacy and rejection rate of MMF and EC-MPS. A total of 611 patients was enrolled from 2014 to February of 2021. Patients were divided based on the use of MMF or EC-MPS at 6 months post-HTx. Patients who were not prescribed MMF or EC-MPS were excluded. Graft survival, all-cause mortality, and treated rejection were compared between the two groups. All statistical analyses were performed using SPSS; characteristics were compared using Pearson chi-square test and survival rate with Kaplan-Meier plot and log-rank test. Results: A total of 510 HTx patients was analyzed (mean age: 51.74 ± 13.16 years, males: 68.2%). At 6 months after HTx, 78 patients were taking EC-MPA (12.8%) and 432 patients were taking MMF (70.7%). The median follow-up was 42.0 months (IQR: 21.7–61.0 months). Post-HTx outcomes including 3-year survival, graft survival, treated rejection, and cardiac allograft vasculopathy (CAV) were comparable between the two groups during follow-up. Conclusion: Notable differences were not observed in treated rejection, graft survival, and all-cause mortality between MMF and EC-MPS groups. Efficacy of EC-MPS was similar to that of MMF in HTx patients during mid-term follow up after HTx.